The Relationship Between Toothbrushing Compliance and The Incidence of Dental Caries in First-Grade Students - Juleha, Juleha; Agata, Annisa; Subardiah, Ida (Java Nursing Journal, 2025)
Background: Oral and dental health is essential to overall well-being, especially in children, where poor hygiene practices can lead to dental caries and long-term health consequences. In Lampung Province, 47.5% of children aged 5–9 years report oral health issues, often due to insufficient tooth brushing compliance. Purpose: This study aimed to examine the relationship between toothbrushing compliance and the incidence of dental caries in first-grade students at SDN 2 Sumberejo in 2024. Methods: A cross-sectional study was conducted using probability sampling with simple random sampling on 93 first-grade students. Tooth brushing compliance was assessed through questionnaires, and the incidence of dental caries was categorized as mild, moderate, or severe. Data analysis employed the Chi-square test to determine the association between brushing habits and caries incidence. Results: Among students with poor brushing compliance, 41.1% experienced severe caries, 19.1% moderate, and 39.7% mild. In contrast, those with good compliance had only 16% severe, 16% moderate, and 68% mild caries. Statistical analysis revealed a significant relationship between tooth brushing compliance and dental caries incidence (p = 0.038). Conclusion: Tooth brushing compliance plays a significant role in preventing dental caries in school-aged children. Parental involvement in educating and supervising proper brushing habits, particularly at night, is vital in reducing caries rates among students. Public health interventions should prioritize early oral hygiene education to promote long-term dental health